STUDENT ATTITUDES TOWARDS NATURAL SCIENCE: REVIEW OF PLEASURES AND CAREER INTERESTS AT JUNIOR HIGH SCHOOL 17 JAMBI CITY - Nirmala Sari; Erika Erika; Neldawati Neldawati (IJIET (International Journal of Indonesian Education and Teaching), 2020)
The research conducted aims to identify students' attitudes toward science subjects through two indicators, namely the pleasure of learning science and career interests in the field of science owned by students at Junior High School 17 Jambi City. The research instrument used was a questionnaire. The subjects of this research were 128 students at Junior High School 17 Jambi city with a total of 128 students. Samples were taken using a total sampling technique. Data were analyzed using descriptive statistics. The results showed that 72 people out of 128 respondents had sufficient attitudes in the pleasure of learning science and also had enough interest in a career in the field of science. The results of this study also showed that when a child likes to study science, the child also has a good interest in a career in the natural sciences.DOI: 10.24071/ijiet.2020.040108